The Liberation of Portuguese Africa, 1961-75
XVII, 393 p. 2 illus., 1 illus. in color.
Keywords: 'This wide-ranging book takes us along the global itineraries of Lusophone Africa's exiled revolutionaries. By anchoring their activities in an archipelago of urban nodes of activism, the chapters here illuminate the strength and fragility of the international networks formed in the struggle against Portuguese imperialism in the midst of the Cold War.' —George Roberts, Lecturer in Modern History, University of Sheffield This book analyses the liberation struggles that took place in the Portuguese colonies of Angola, Mozambique, Guinea, Cabo Verde, and São Tomé e Príncipe during the second half of the twentieth century, highlighting how they unravelled and challenged colonialism in the international sphere. Activists established headquarters and training camps in various exile settings that were instrumental in their struggle for independence. Exile settings were places where the liberation movements worked with host countries, accessed representatives of foreign countries, made connections with nonstate actors and networks of support, and received political and military training. The complex networks of support formed by protestors around the globe operated on a transnational scale, using urban centres as sites of activism and arenas to promote a multiplicity of connections. Bringing together contributions from a range of skilled authors, the book explores selected hubs around the globe including those based in Kinshasa, Dar es Salaam, Cairo, Moscow, Beijing, New York, London, Paris, and São Paulo. Taking a comparative approach, this collection sheds light on the infrastructures of solidarity that were established by activists around the world, and highlights the transnational circulation of ideas around anticolonialism. Pedro Aires Oliveira is an Associate Professor in the History Department of the School of Humanities and Social Sciences at NOVA University of Lisbon, Portugal, where he is also a Researcher in the Institute of Contemporary History. Fernando Tavares Pimenta is a Researcher and President of the Scientific Council of the Centro de Estudos de História do Atlântico-Alberto Vieira (CEHA-AV/DRABL) in Madeira Island, as well as an Associate Fellow of the Institute of Contemporary History, NOVA University of Lisbon, Portugal. Aurora Almada e Santos is a Researcher in the Institute of Contemporary History, at NOVA University of Lisbon, Portugal.